The impact of innovation on labour productivity growth in European industries: Does it depend on firms' competitiveness strategies? - Francesco Bogliacino; Mario Pianta (European Commission, Joint Research Centre (JRC), 2009)
The diversity of technological activities that contribute to growth in labour productivity is examined in this paper for manufacturing and services industries in eight major EU countries. We test the relevance of the two major strategies of technological competitiveness (based on innovation in products and markets) or cost competitiveness (relying on innovation in processes and machinery) and their impact on economic performances. We propose models for the determinants of changes in labour productivity and we carry out empirical tests both for both the whole economy and for the four Revised Pavitt classes that group manufacturing and services industries with distinct patterns of innovation. Tests are carried out by pooling industries, countries and three time periods, using innovation survey data from CIS 2, 3 and 4, linked to economic variables.The results confirm the strong diversity of the mechanisms leading to productivity growth in Europe, with different roles of sector-specific technological activities developed in the pursuit of the strategies of technological competitiveness and cost competitiveness. In all empirical tests, for all industries as well as for each revised Pavitt class, we find a presence of both strategies, with a relevance and impact that is specific for each subgroup of industries. Economic performances in European industries appear as the results of different innovation models, with strong specificities of the four Revised Pavitt classes (i.e. "Science Based industries", "Scale and Information Intensive industries", "Specialised Suppliers industries" and "Suppliers Dominated industries").A number of policy lessons emerge from our findings. Policies aiming at greater labor productivity growth may have to take into account the different mechanisms resulting from technological and cost competitiveness strategies, and the different relevance that they have in industry groups. Efforts to introduce new processes have emerged as a strong aspect of innovative activities in all industries, but their impact on productivity growth is likely to be inferior to that of a search for new products and markets, typical of "Science Based" and "Specialised Suppliers" industries alone. Policies may be more effective when they focus on the latter type of efforts. As the dynamics of demand plays a strong role in the potential for productivity growth, innovation policies should also develop a stronger integration with industrial and macroeconomic policies.
Keywords: O31; O33; O41; 330; Innovation; Labour Productivity; Industry Taxonomies; Technological and Cost Competitiveness